The Influence of Facilities and Tourist Attractions on Interest in Revisiting Jambak Sand Beach, Padang City - Rosy Witrin; Susanti, Retnaningtyas (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The Indonesian tourism industry has experienced significant development in recent years, especially the marine tourism sector, a favorite destination for domestic and foreign tourists. This study aims to analyze the influence of tourism facilities and tourist attractions on the interest in revisiting Pasir Jambak Beach, Padang City. This research methodology uses a quantitative descriptive approach with multiple linear regression analysis of 96 secondary data samples from 2023-2024, obtained from the Padang City Tourism Office. The study showed that tourist attractions had a dominant influence with a regression coefficient of 0.658 (sig. 0.000), contributing 43.3% to the interest in revisiting. Tourism facilities had a significant effect with a coefficient of 0.542 (sig. 0.000), contributing 29.4%. Simultaneously, these two variables were able to explain the variance in the interest in revisiting by 72.4% (R² = 0.724, F = 123.567, sig. 0.000). It can be concluded that the superiority of the natural tourist attractions of Pasir Jambak Beach is the main determinant of tourist loyalty, while tourist facilities function as supporting factors for the realization of an optimal tourist experience. Implications: Tourist destination managers should prioritize the development of tourist attractions based on local uniqueness while maintaining the quality standards of supporting infrastructure.